Degradation of Interfacial Bond for FRPs Near-Surface Mounted to Concrete Under Fatigue: An Analytical Approach - Xun Wang; Lijuan Cheng (Fibers)
In this study, an analytical model was developed for the local bond degradation behavior between a near-surface mounted (NSM) fiber-reinforced polymer (FRP) and concrete under fatigue loading. A trilinear local bond stress–slip relationship was adopted to characterize the fundamental bond behavior at the FRP-epoxy-concrete interface at different stages of elastic, softening and debonding. A series of post-fatigue direct pull-out tests (DPTs) of NSM FRP-bonded concrete blocks was conducted to provide the local bond degradation laws for the analytical model. The bond region was discretized into finite elements to include the effect of bond degradation to different extents, and a closed-form solution was derived by virtue of appropriate boundary conditions in each fatigue cycle. The model is capable of predicting the FRP strain distribution, local bond stress distribution and relative slip development at a targeted number of fatigue cycles. The reliability of the analytical model was confirmed by experimental data, and its sensitivity to various parameters such as local bond strength, the residual bond strength ratio and Young’s modulus of FRP reinforcement was also assessed in this study.